Positional changes in the hyoid bone, hypopharynx, cervical vertebrae, and Cranium before and after correction of glosso-larynx (CGL) - Susumu Mukai (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
Introduction: Respiratory inhibition by ankyloglossia with deviation of the epiglottis and larynx (ADEL) was thought to be caused by tongue muscles. But to explain this effect by the tongue muscles alone was unreasonable. Thorough investigations of ADEL by head and neck X-rays were performed. The surveillance revealed the existence of an important organ necessary in the neck to separate air and food as well as to regulate respiration. Methods: Changes in the vertebrae, cranium, hyoid bone, and the width of the hypopharynx were compared by simple lateral X-radiographs before and after correction of the glosso-larynx (CGL) in 116 adults.  Results: The face was held straight, the hypopharynx was widened, and the hyoid bone moved about half the size of a vertebra down and forward. Discussion: This study concluded that an organ in the neck that separates air and food as well as regulates respiration is necessary. The structure of the organ might consist of the styloid process, the hyoid bone, and a part of the trachea. It must perform up and down movements at any time. The structure was named "hyoid bone composition (HBC)". The HBC originates from the 2nd gill, and belongs to the respiratory system. The fi rst role of the HBC is protection of the respiratory system. Upper force to the HBC inhibits respiration and vice versa.  In humans there is a constant upper force to the HBC by the tongue muscles. This condition is thought to be ADEL. CGL is a surgery in which the genioglossus muscles are cut and the force to the HBC is released. As a result, respiration is increased and symptoms and signs of ADEL are ameliorated. Conclusion: The HBC is necessary in the human neck. It moves down and forward after CGL. Respiration increases by movement of the HBC. The face is also held straight by changes in the center of gravity. (309 words).